Concomitant Distal Radioulnar Joint Disruption in Distal End Radius Fracture Cases Admitted to Emergency Ward Hasan Sadikin Hospital January 2013 – December 2015 - Tody Pinandita; Herry Herman; Yoyos Dias Ismiarto (Fakultas Kedokteran Universitas Lambung Mangkurat, 2019)
Abstract: The distal end radius and ulna is an integral part of the wrist joint and preservation of its normal anatomy is essential for the mobility of the wrist. The most common cause of residual wrist disability after distal end radius fractures is the disruption of distal radioulnar joint (DRUJ). Early recognition and management in the acute stage aim at the anatomic reconstruction of the DRUJ in an effort to reduce incidence of chronic pain and loss of wrist motion. The purpose of this study is to identify the prevalence of accompanying DRUJ in distal end radius fracture cases, highlighting its significance in occurance. This was a retrospective study with an analytic descriptive method and data from January 2013-December 2015 taken from medical records of Dr. Hasan Sadikin Hospital. From research, we found 74 cases of distal end radius fracture. The most common injured wrist were dominant hand as 46 cases (62,2%), and non-dominant hand as 28 cases (37,8%). From all data, DRUJ disruption were marked as 37 cases (50%). Extraarticular fracture with concomitant DRUJ disruption were marked in 3 cases (8,1%) and in intraarticular involvement were 34 cases (91,9 %). From this study, we can conclude that half of the distal end radius fracture cases, especially intraarticular, were accompanied by DRUJ disruption. This should be an issue to be concerned by the physician when evaluating distal end radius fracture cases and to perform proper treatment.